GEOCHEMISTRY OF ROCKS FROM VOLCANIC-PLUTONIC ASSOCIATIONS AT THE KARAMKEN GOLD-SILVER DEPOSIT, RUSSIAN NORTHEAST - Zakharov M.N.; Kravtsova R.G. (My University, 2001)
New data on the trace element distribution in rocks of volcanic-plutonic associations from the vicinity of the Karamken gold-silver deposit are reported. The deposit is localized in the outer zone of the Cretaceous Okhotsk-Chukotka volcanic belt. The locally widespread Cretaceous calc-alkaline rocks compose a continuous series from high-alumina basalt to rhyolite. The Paleogene lamprophyre dikes are derivatives of alkali picrite magma. The distribution of major and trace elements in the rocks and correlations between elements indicate that the primary magma fractionation was the principal petrogenetic process. The early mineral assemblages of basalt and andesite crystallized from dry deep-seated melts, whereas the late assemblages are the products of water-rich magma crystallization in shallow-seated chambers. The diorite porphyry and related breccia that hosts the Au-Ag mineralization are considered in detail.
Keywords: Paleogene; Cretaceous; Кайнозой::Палеоген; Mesozoic::Cretaceous; Cenozoic::Paleogene; Мезозой::Меловая